2004
DOI: 10.1111/j.1399-0012.2004.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype prevalence, viral load and outcome of hepatitis B virus precore mutant infection in stable patients and in patients after liver transplantation

Abstract: The chronic precore mutant HBV-infected patients were characterized as follows: (i) genotype D was the most frequent genotype, (ii) the HBV genotype distribution was similar in patients with stable infection and after liver transplantation, (iii) viral load at recurrence was significantly higher than in stable infection, and (iv) HBV genotype was unrelated to the development of recurrence or lamivudine resistance in the tested population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…HBV can be classified into eight genotypes (A–H) (17, 18). In our experience in the Mediterranean basin, the predominant genotype is D (96%) (19). HBV genotypes may affect the rate of recovery after acute infection, the progression of chronic liver disease, and the response to antiviral treatment.…”
Section: Discussionmentioning
confidence: 75%
“…HBV can be classified into eight genotypes (A–H) (17, 18). In our experience in the Mediterranean basin, the predominant genotype is D (96%) (19). HBV genotypes may affect the rate of recovery after acute infection, the progression of chronic liver disease, and the response to antiviral treatment.…”
Section: Discussionmentioning
confidence: 75%
“…Ben-Ari et al (Table 8) reported no statistically significant difference in genotype prevalence in patients undergoing liver transplantation and stable patients. 112 Girlanda et al (Table 8) reported that genotypes A and D were not significant predictors of transplantation outcomes. 61 Tables 4 and 8 summarize the clinical implications and correlation between HBV genotypes and liver transplantation outcomes.…”
Section: Liver Transplantationmentioning
confidence: 97%
“…Different HBV genotype on recurrence rate have been discussed, but as shown in two recent studies, difference in the recurrence rate between different HBV genotypes were not observed [15,16].…”
Section: Hbv Reinfection After Oltmentioning
confidence: 96%